Marine tardigrades of the Bahamas with the description of two new species and updated keys to the species of Anisonyches and Archechiniscus - Bartels, Paul J.; Fontoura, Paulo; Nelson, Diane R. (Zootaxa, 2018)
This is the first survey of subtidal marine tardigrades from the Bahamas, and we compare our results with earlier studies of Bahamian intertidal habitats. In 2011 and 2014 we collected 60 subtidal sand samples from Bimini, the Berry Islands, New Providence, Eleuthera, and the Exumas. We found 11 species only one of which, Dipodarctus subterraneus (Renaud-Debyser, 1959), had been found in the previous intertidal Bahamian collections. Thus, 10 species are new records for the Bahamas, and four of these are new to science. We describe two of the new species (Archechiniscus bahamensis sp. nov. and Anisonyches eleutherensis sp. nov.). Additional material is needed for a conclusive identification of the undescribed species of Batillipes and Florarctus. Based on examination of the holotype of Anisonyches diakidius Pollock, 1975, we redescribe this species and give an emended diagnosis of the genus and the species. We also provide new keys to the species in the genera Archechiniscus and Anisonyches. A Chao2 species richness estimate indicated that our sampling effort was extensive and probably recovered most common species. Correlations of abundance and diversity indices with regard to depth, distance to nearest shore, and sediment grain size were not significant.